2008
DOI: 10.1088/0004-637x/690/2/l122
|View full text |Cite
|
Sign up to set email alerts
|

THE DETECTION OF INFRARED SiS BANDS IN SPECTRA OF S STARS

Abstract: We present Spitzer spectra of S stars, which are cool evolved stars with a C/O ratio near unity, some of which have enhanced s-process abundances. We present the detection of a strong and unusual band in the mid-infrared, at 13 μm, within the N-band window. Using quantum-chemically calculated line lists, and model spectra, we identify this band as the fundamental rovibrational band of SiS. Detection of the overtone band at 6.7 μm confirms the identification. Fitting the line profile shows that the molecule is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Previous studies of this sample have already led to the identification of the fundamental ro-vibrational band of SiS at 13 µm and its first overtone at 6.7 µm in absorption (Cami et al 2009) and in emission (Sloan et al 2011). Furthermore, four stars in this sample show the typical hydrocarbon emission features on top of an oxygen-rich photosphere (Smolders et al 2010).…”
Section: Introductionmentioning
confidence: 62%
“…Previous studies of this sample have already led to the identification of the fundamental ro-vibrational band of SiS at 13 µm and its first overtone at 6.7 µm in absorption (Cami et al 2009) and in emission (Sloan et al 2011). Furthermore, four stars in this sample show the typical hydrocarbon emission features on top of an oxygen-rich photosphere (Smolders et al 2010).…”
Section: Introductionmentioning
confidence: 62%
“…The radiative transfer equation is solved monochromatically using pre-tabulated extinction coefficients as a function of temperature, density, and wavelength. The lookup tables were computed for the same chemical compositions as the RHD simulations using the same extensive atomic and molecular continuum and line opacity data as the latest generation of MARCS models (Gustafsson et al 2008) with the addition -with respect to Table 2 of Gustafsson's paper -of the SiS molecule (Cami et al 2009), which is particularly important for the far-infrared region of the spectrum. While the sources of line opacities used in the RHD simulations of Magic et al (2013) and in OPTIM3D are the same, the data for the continuum opacities are almost the same: Hayek et al (2010) reported that the data used in RHD simulations are mostly identical to those used in the MARCS models, but include additional bound-free data from the Opacity Project and the Iron Project (Trampedach et al, priv.…”
Section: Three-dimensional Radiative Transfermentioning
confidence: 99%
“…comm.) as an update after the new energy levels calculated by Ram et al (2010a,b); H 2 O lines were taken from Barber et al (2006); SiO lines were taken from Langhoff & Bauschlicher (1993); MgH lines were taken from Skory et al (2003); OH were taken from Goldman et al (1998), SiS were taken from Cami et al (2009) and OH ones from the HITRAN database (Rothman & Gordon 2009). The atomic lines were taken from the VALD v-0.4.4 database (Kupka et al 2000).…”
Section: Observed Data and Line Listsmentioning
confidence: 99%